2018
DOI: 10.1530/jme-18-0078
|View full text |Cite
|
Sign up to set email alerts
|

ADSC-conditioned media elicit an ex vivo anti-inflammatory macrophage response

Abstract: Obesity-associated inflammatory mechanisms play a key role in the pathogenesis of metabolic-related diseases. Failure of anti-inflammatory control mechanisms within adipose tissue and peripheral blood mononuclear cells (PBMCs) have been implicated in disease progression. This study investigated the efficacy of allogeneic adipose tissue-derived mesenchymal stem cells conditioned media (ADSC-CM) to counteract persistent inflammation by inducing an anti-inflammatory phenotype and cytokine response within PBMCs de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Adipose stem cells exhibit characteristics similar to MSCs. A study exploring the efficacy of allogeneic adipose tissue‐derived mesenchymal stem cell conditioned media (ADSC‐CM) to counteract persistent inflammation firstly illustrated the therapeutic potential of ADSC‐CM to restore the inflammatory balance in immune‐compromised obese individuals . ADSC‐Exos also displayed protective effects for osteoarthritis (OA) through the possible mechanism of downregulating senescence‐associated β‐galactosidase activity, thus reducing the production of inflammatory mediators .…”
Section: Effects Of Adsc‐exos In Skin Wound Healingmentioning
confidence: 99%
“…Adipose stem cells exhibit characteristics similar to MSCs. A study exploring the efficacy of allogeneic adipose tissue‐derived mesenchymal stem cell conditioned media (ADSC‐CM) to counteract persistent inflammation firstly illustrated the therapeutic potential of ADSC‐CM to restore the inflammatory balance in immune‐compromised obese individuals . ADSC‐Exos also displayed protective effects for osteoarthritis (OA) through the possible mechanism of downregulating senescence‐associated β‐galactosidase activity, thus reducing the production of inflammatory mediators .…”
Section: Effects Of Adsc‐exos In Skin Wound Healingmentioning
confidence: 99%
“…Thangarajan et al 24) suggested that the paracrine effect of the ADSCs on the wound healing process has the effect of inducing the endogenous stem cells in the injured region to initiate the healing process. Furthermore, It was suggested that the ADSC transplantation had the effect of reducing the inflammatory response [25][26][27] . It has been reported that ADSCs increase the production of VEGF under hypoxic culture conditions 13,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Failure of anti-inflammatory control mechanisms within adipose tissue and peripheral blood mononuclear cells (PBMCs) have been implicated in disease progression. More importantly, ADSCs can distinguish between M1 and M2 macrophages and inducing their polarization into the anti-inflammatory profile M2 [ 34 ]. Also, ADSCs ensure the inactivation of T cells through secreting IL-10, TGF-β and impair B lymphocytes function [ 35 ].…”
Section: Adipose Derived Stem Cells (Adscs) and Their Exosomes Therapeutic Usementioning
confidence: 99%